Investigation and Evaluation of Potential Options to Determine the Methane Gas - Cakir, Ali Kemal (Salehan Institute of Higher Education, 2018)
Izmir has been one of the cities in our country which firstly began to implement a regular solid waste disposal system with the operation of Harmandali Landfill Facility in 1992. An important part of municipal solid waste produced in contiguous area of Izmir during the period of 25 years was disposed in this facility in order to minimize any possible problems on health and environment caused from that solid waste. The most important factor for deciding on the energy potential of landfill is the amount of landfill methane gas in the landfill area. There are several approaches used to determine the amount of landfill gas. We used one method (When the facility conditions are taken into account (moisture, waste water, landfill leachate etc.) that it is the most appropriate method) and one Literature-Based Approximate Forecast to determine the amount of the landfill gas in Harmandali Landfill. This method is Multi-Phase method. The main objective of this study is to investigate the use of landfill gas as potential energy and electricity provided from municipal solid waste (domestic, industrial, medical waste and sewage sludge) stored regularly in Harmandali Solid Waste Landfill Area, within the boundaries of the contiguous area of Izmir.